Strategi Pengembangan Sektor Pertanian Di Desa Ngompro, Kabupaten Ngawi: Analisis SWOT, Sektor Pertanian Desa, Strategi Pengembangan - Suhardjito, Suhardjito (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
Ngompro Village has the greatest potential in the agricultural sector, this is strengthened by the large number of people working in the agricultural sector, namely 2331 residents. However, the agricultural sector in the village is still not able to provide a good enough contribution because of the various problems it faces, both originating from the internal and external conditions of the village. This study used eight informants consisting of three lecturers from the Soerjo University of Ngawi, staff of agricultural institutions, heads of agricultural extension officers, heads of villages, heads of Gapoktan, and heads of farmer groups. The data obtained were analyzed using the IFAS matrix, EFAS, and the SWOT matrix. The results showed that there were nine supporting factors and fife inhibiting factors in the agricultural development of Ngompro Village. In addition, the internal factor that has the highest score is Ngompro Village having a BUMDes institution and an agricultural extension agency as a companion in agricultural sector activities, and for external factors, the highest score is that there is a national development plan in Ngompro Village. The strategies that are prioritized and can be implemented are the use of modern technology in cooperation activities, there is a performance collaboration between farmer group leaders and educational institutions, there is broad marketing access inside and outside the village, and farmers and BUMDes institutions can collaborate to seek more efficient and profitable crop marketing network.